The relationship between polyphenols and miRNAs: A novel therapeutic strategy for metabolic associated fatty liver disease - EREN, FATİH; GÜNEŞ, FATMA ESRA (My University, 2021)
Metabolic-associated fatty liver disease (MAFLD) is a public health problem that is increasingly recognized, currently affecting up to a quarter of the world\"s adult population. Although a biopsy is the current gold standard to diagnose MAFLD, there are potentially serious complications, making it inadequate. Thus far, noninvasive methods have not been able to determine the stage and the subtype of MAFLD. The development and prognosis of MAFLD are modulated by epigenetic factors, including microRNAs (miRNAs), which may be potential biomarkers for MAFLD. Polyphenols, found in many fruits and vegetables, may be useful, as they alter gene expression with epigenetic factors, such as miRNAs. This review presents an overview of the relationship between polyphenols and miRNAs in MAFLD. The literature suggests that miRNAs could be used as a diagnostic method for MAFLD, especially miRNA-122 and miRNA-34a. However, though it has been demonstrated that polyphenols may contribute to improving MAFLD, to our knowledge, no study to date has shown the relationship between polyphenols and miRNAs in MAFLD. The exact mechanisms of polyphenols on miRNAs in MAFLD remain unclear. Future studies may provide hope for diet therapy for MAFLD patients as well as the development of polyphenol-related foods or drugs that target miRNAs to treat MAFLD.
Keywords: Tıp; Dahili Tıp Bilimleri; İç Hastalıkları; Gastroenteroloji-(Hepatoloji); Sağlık Bilimleri; Medicine; Internal Medicine Sciences; Internal Diseases; Gastroenterology and Hepatology; Health Sciences; GASTROENTEROLOJİ VE HEPATOLOJİ; Klinik Tıp; Klinik Tıp (MED); GASTROENTEROLOGY & HEPATOLOGY; CLINICAL MEDICINE; Clinical Medicine (MED); Hepatoloji; Gastroenteroloji; Hepatology; Gastroenterology; Metabolic-associated fatty liver disease; microRNA; polyphenols; NONALCOHOLIC STEATOHEPATITIS; CHOLESTEROL-METABOLISM; CIRCULATING MICRORNAS; LIPID-ACCUMULATION; INSULIN-RESISTANCE; DOWN-REGULATION; IN-VIVO; EXPRESSION; MIR-122; ACID; Polyphenols; metabolic associated fatty liver disease; microRNA